Molecular insights into the progression of crystalline silica‐induced pulmonary toxicity in rats. Issue 4 (19th March 2012) - Sellamuthu, Rajendran; Umbright, Christina; Roberts, Jenny R.; Cumpston, Amy; McKinney, Walter; Chen, Bean T.; Frazer, David; Li, Shengqiao; Kashon, Michael; Joseph, Pius
ABSTRACT Identification of molecular target(s) and mechanism(s) of silica‐induced pulmonary toxicity is important for the intervention and/or prevention of diseases associated with exposure to silica. Rats were exposed to crystalline silica by inhalation (15 mg m−3, 6 h per day, 5 days) and global gene expression profile was determined in the lungs by microarray analysis at 1, 2, 4, 8 and 16 weeks following termination of silica exposure. The number of significantly differentially expressed genes (>1.5‐fold change and <0.01 false discovery rate P‐value) detected in the lungs during the post‐exposure time intervals analyzed exhibited a steady increase in parallel with the progression of silica‐induced pulmonary toxicity noticed in the rats. Quantitative real‐time PCR analysis of a representative set of 10 genes confirmed the microarray findings. The number of biological functions, canonical pathways and molecular networks significantly affected by silica exposure, as identified by the bioinformatics analysis of the significantly differentially expressed genes detected during the post‐exposure time intervals, also exhibited a steady increase similar to the silica‐induced pulmonary toxicity. Genes involved in oxidative stress, inflammation, respiratory diseases, cancer, and tissue remodeling and fibrosis were significantly differentially expressed in the rat lungs; however, unresolved inflammation was the single most significant biological response to pulmonary exposure to silica. Excessive mucus production, as implicated by significant overexpression of the pendrin coding gene, SLC26A4, was identified as a potential novel mechanism for silica‐induced pulmonary toxicity. Collectively, the findings of our study provided insights into the molecular mechanisms underlying the progression of crystalline silica‐induced pulmonary toxicity in the rat. Published 2012. This article is a US Government work and is in the public domain in the USA.